2009
DOI: 10.1038/sj.bjc.6605425
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of the nitroimidazole hypoxia marker SR4554 using 19F magnetic resonance spectroscopy

Abstract: Background: SR4554 is a fluorine-containing 2-nitroimidazole, designed as a hypoxia marker detectable with 19 F magnetic resonance spectroscopy (MRS). In an initial phase I study of SR4554, nausea/vomiting was found to be dose-limiting, and 1400 mg m −2 was established as MTD. Preliminary MRS studies demonstrated some evidence of 19 F retention in tumour. In this study we investigated higher doses of SR4554 and intrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The pharmacokinetic and toxicity profiles appear to be favorable for use as a hypoxia marker. More recently, a mean retention index of 13.6 in human neoplasms has been reported, compared to the retention index of 4.1 found in plasma samples obtained simultaneously with the spectroscopic measurement, revealing the presence of hypoxia in those tumours (128).…”
Section: Nitroimidazole Drugsmentioning
confidence: 98%
“…The pharmacokinetic and toxicity profiles appear to be favorable for use as a hypoxia marker. More recently, a mean retention index of 13.6 in human neoplasms has been reported, compared to the retention index of 4.1 found in plasma samples obtained simultaneously with the spectroscopic measurement, revealing the presence of hypoxia in those tumours (128).…”
Section: Nitroimidazole Drugsmentioning
confidence: 98%
“…Its accumulation can be used to report on hypoxia in vivo with 19 F MRS (Procissi et al, 2007). Very few first-in-human studies have been performed so far (Lee et al, 2009). The nitroimidazole hypoxia marker SR4554 was tested in 26 patients in various malignancies, with a predominance of gastrointestinal stromal tumors, head and neck cancer, and melanoma.…”
Section: Imaging and Pm/theranostics Of The Physiological Microenvmentioning
confidence: 99%
“…Tumors that were at least 3 cm in size and no more than 4 cm depth were investigated to allow acquisition of 19 F MRS data with a surface coil. While the study showed the feasibility of using MRS to study the retention of the probe in some tumors, it also highlighted the low sensitivity of MRS compared to PET (Lee et al, 2009). …”
Section: Imaging and Pm/theranostics Of The Physiological Microenvmentioning
confidence: 99%
“…The spatial distribution of the probe can be visualized with 19 F MR spectroscopic images overlaid with anatomic images [58]. Phase I studies of SR-4554, a fluorinated 2-nitroimidazole, demonstrated that 19 F MR spectra can detect retention of the probe in tumors after intravenous injection [59,60]. Hypoxia in tumors can also be detected with 19 F MRS of hexafluorobenzene, a reporter molecule with an oxygen-dependent T 1 relaxation rate [56].…”
Section: In Vivo Preclinical and Clinical Studies Stromal Cell–cancer Cmentioning
confidence: 99%